Pelatihan Pemrograman Web Pada Siswa Kelas XI Jurusan RPL SMKN 1 Pringgasela - Hidayat, Muh. Adrian Juniarta; Putra, Yupi Kuspandi; Fathurrahman; Nurhidayati (Jurnal Teknologi Informasi untuk Masyarakat, 2025)
The training for students majoring in software engineering aims to help students improve their expertise in web programming to prepare them for the world of work in the field of computer science programming. Currently, technical skills in programming are in great demand, especially for students majoring in Software Engineering because having a diploma alone is not enough to enter the world of work. Therefore, the team from the information systems study program, Faculty of Engineering, Hamzanwadi University, held training for vocational high school students with the aim of making a real contribution to society as part of the tridharma of higher education. The target of this activity is class XI students majoring in Software Engineering at SMKN 1 Pringgasela who are the main partners. The target and output of this activity is to increase students' skills in the field of web programming. The method used is Participatory Learning and Action (PLA). This activity is carried out by providing training and mentoring in theory and practice. With this expertise competency training, especially in the field of web programming, it is hoped that it can help students prepare themselves before entering the world of work in the future